RECREATION OF THE CONCEPT OF “LOVE” IN TRANSLATIONS OF SHAKESPEARE'S SONNETS INTO UZBEK (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article discusses the re-creation of the concept of “love” in the Uzbek translations of sonnets, which are an integral part of Shakespeare's work. The term “concept” is also discussed, as well as its origins and place in translation studies. The study of the concept of “love” and the extent to which the translator was able to convey the concept of love used in the sonnets in the Uzbek language will be analyzed.